Multidisciplinary management of chronic refractory pain in autosomal dominant polycystic kidney disease. Issue 3 (25th May 2022) - van Luijk, Franka; Gansevoort, Ron T; Blokzijl, Hans; Groen, Gerbrand J; de Haas, Robbert J; Leliveld, Anna M; Meijer, Esther; Perdok, Joke M; Stellema, Ruud; Wolff, Andreas P; Casteleijn, Niek F
ABSTRACT: Background: Chronic pain is often difficult to manage in autosomal dominant polycystic kidney disease (ADPKD) patients and sometimes even leads to nephrectomy. We analyzed the long-term efficacy of our innovative multidisciplinary protocol to treat chronic refractory pain that aims to preserve kidney function by applying among other sequential nerve blocks. Methods: Patients were eligible if pain was present ≥3 months with a score of ≥50 on a visual analog scale (VAS) of 100, was negatively affecting quality of life and if there had been insufficient response to previous therapies, including opioid treatment. Treatment options were, in order, analgesics, cyst aspiration and fenestration, nerve blocks and nephrectomy. Results: A total of 101 patients were assessed in our clinic (mean age 50 ± 11 years, 65.3% females). Eight patients were treated with medication, 6 by cyst aspiration or fenestration, 63 by nerve blocks and 6 received surgery as the first treatment option. Overall, 76.9% experienced a positive effect on pain complaints shortly after treatment. The VAS score was reduced from 60/100 to 20/100 (P < 0.001) and patients decreased their number of nonopioid and opioid analgesics significantly (P < 0.001, P = 0.01, respectively). A substantial number of the patients ( n  = 51) needed additional treatment. At the end of follow-up in only 13 patients (12.9%) was surgical intervention necessary: 11 nephrectomies (of which 10 were in patients already on kidney function replacement treatment), 1 liver transplantation and 1 partial hepatectomy. After a median follow-up of 4.5 years (interquartile range 2.5–5.3), 69.0% of the patients still had fewer pain complaints. Conclusions: These data indicate that our multidisciplinary treatment protocol appears effective in reducing pain in the majority of patients with chronic refractory pain, while postponing or even avoiding in most patients surgical interventions such as nephrectomy in most patients. Graphical Abstract: